The Effect of Classical Music Therapy on Reducing Pain Scale in Post-Cesarean Section Patients - Suriana; Herman, Erlin (Fakultas Kedokteran, Universitas Papua, 2025)
Cesarean section is a surgical procedure that can lead to postoperative pain due to disrupted tissue continuity. Pain management generally involves the use of analgesics; however, non-pharmacological therapies such as classical music may serve as complementary interventions to reduce pain perception. This study aimed to evaluate the effect of classical music therapy on reducing the pain scale in postpartum women following cesarean section. This research employed a quasi-experimental design using a one-group pre-test and post-test with control group approach, involving 30 postpartum women selected through total sampling. The intervention consisted of playing classical music for 20 minutes per day over two consecutive days, with pain levels measured using the Numeric Rating Scale (NRS) before and after the intervention. The results showed a significant difference in pain scores before and after classical music therapy (p < 0.05), indicating the therapy’s effectiveness in reducing post-cesarean section pain. Therefore, classical music therapy may serve as an effective non-pharmacological approach to managing postoperative pain in postpartum women.